Distribution of polyethylenimine in zebrafish embryos - Róża Chmielewska; Maciej Gawlak; Magdalena Bamburowicz-Klimkowska; Magdalena Popławska; Ireneusz P. Grudziński (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Polyethylenimine (PEI) plays important roles in the pharmaceutical design of non-viral gene delivery systems. Due to a set of unique physicochemical properties this cationic polymer has a great potential in modern gene therapies. Objective. The aim of the present study was to determine the distribution of branched PEI (0.8 kDa) in zebrafish embryos (Danio rerio). Material and methods. Zebrafish embryos at 3 hours post-fertilization (hpf) were incubated with PEI (10 μg/ml) for 24 and 48 hours and studied using the confocal laser microscopy. Results. The obtained results show that PEI effectively distributed into the layers of the chorion and yolk sac in developing embryos due to first 24 hours of exposure. In contrast, PEI was found in the yolk, head, trunk and tail of the embryos due to prolonged treatments (48 hours). Conclusion. The study evidences a high distribution of the branched PEI (0.8 kDa) polymer in the zebrafish embryo tissues.